The effects of augmented feedback on motor skill learning in shooting: A feedback training intervention among inexperienced rifle shooters - Mononen, K. (Studies in Sport, Physical Education and Health, 2007)
The present study focused on examining the effects of knowledge of performance (KP) on motor skill performance and learning within the context of precision rifle shooting. KP was based on the on-target trajectory of the alignment of the rifle, accompanied by visual or auditory feedback. The effects of KP were evaluated in terms of shooting accuracy, rifle stability, and postural balance. For this purpose, male conscripts (n=58) with limited shooting experience were randomly assigned to the one of the following five groups: a group receiving knowledge of results (KR) with visual KP after each trial, a group receiving KR with visual KP after 50% of the trials, a group receiving KR with auditory KP during 50% of the trials, a group with KR only after each trial, and a non-training control group. The four experimental groups accomplished a 4-week training period during which feedback was provided. No-feedback retention tests were administered at 2, 10, and 40 days after acquisition. The participants with auditory KP during 50% of the trials showed the highest shooting accuracy in all the retention tests. Visual KP after each trial benefited shooting accuracy when compared to reduced frequency of visual KP, or no KP. Furthermore, the participants with high frequency of visual KP performed with significantly lower maximal amplitude of sway when compared to the KR group. The indices for rifle stability did not differentiate among the groups with different visual KP conditions. In all, the present study demonstrated that augmented feedback describing the essential aspect of shooting performance was beneficial for the performance and learning of precision shooting. In particular, auditory KP during 50% of the trials seemed to promote shooting performance among inexperienced shooters. It is concluded that auditory feedback provided concurrently with aiming promoted a shooter's self-initiated error detection and correction abilities by directing his attention to the critical components of psychomotor regulation.